Odyssey Self Reflection - knitting technique / Faculty of Art and Design UiTM Cawangan Sarawak - Mohd Rathi, Mohd Razif (Perpustakaan Tun Abdul Razak, PTAR Universiti Teknologi Mara Cawangan Sarawak, 2021)
The design of knitting techniques had encouraged me to create works of art consisting of drawing, painting, printmaking and sculpture. The concept of my artworks was significantly associated with the famous post impression paintings, the predominantly French art movement. The elements and principles in the artworks highlighted the form of knitting technique where a ball of yarn is manipulated using a needle to create a fabric. I applied ready-made materials for my sculpture such as wood and yarn. I used mixed techniques for the printmaking artwork which were intaglio and stencil.